Single-centre parental survey of paediatric rehabilitation services for children with cerebral palsy. Issue 1 (30th March 2021) - Bican, Rachel; Ferrante, Rachel; Hendershot, Sarah; Heathcock, Jill C
Abstract : Cerebral palsy (CP) is the most common childhood motor disability. The dose of usual care for rehabilitation therapies is unknown. The purpose of this study was to describe current dosage of rehabilitation services for children with CP recruited from a paediatric hospital system in the USA. 96 children with CP were included in this cross-sectional survey. Parents reported frequency, intensity, time and type of therapy services. Weekly frequency was the most common. Children with CP received 0.9–1.2 hours/month of each discipline in the educational setting and 1.5–2.0 hours/month in the clinical setting, lower than the recommendations for improvements in motor skills.